Do Freshwater Fish Eat Microplastics? A Review with A Focus on Effects on Fish Health and Predictive Traits of MPs Ingestion - Silvia Galafassi (Water, 2021)
Microplastics (MPs) have received increasing attention in the last decade and are now considered among the most concerning emerging pollutants in natural environments. Here, the current knowledge on microplastic ingestion by wild freshwater fish is reviewed with a focus on the identification of possible factors leading to the ingestion of MPs and the consequences on fish health. Within the literature, 257 species of freshwater fishes from 32 countries have been documented to ingest MPs. MPs ingestion was found to increase with rising level of urbanization, although a direct correlation with MPs concentration in the surrounding water has not been identified. MPs ingestion was detected in all the published articles, with MPs presence in more than 50% of the specimens analyzed in one study out of two. Together with the digestive tract, MPs were also found in the gills, and there is evidence that MPs can translocate to different tissues of the organism. Strong evidence, therefore, exists that MPs may represent a serious risk for ecosystems, and are a direct danger for human health. Moreover, toxicological effects have also been highlighted in wild catches, demonstrating the importance of this problem and suggesting the need for laboratory experiments more representative of the environmental situation.